A 22-Year Survey of Leishmaniasis Cases in a Tertiary-Care Hospital in an Endemic Setting - Calderaro, Adriana (MDPI, 2014)
The northward spread of leishmaniasis from Mediterranean to Continental Europe affects our area where it is typically associated with Leishmania infantum infection. In this study a 22-year survey was performed in patients (including both patients with and without history of travel through endemic areas other than Italy) attending the University Hospital of Parma, Northern Italy, in order to make a contribution to describe the cases of the visceral leishmaniasis (VL) and cutaneous leishmaniasis (CL) diagnosed in this area. One hundred fifty-six samples from 134 patients with clinical suspicion of leishmaniasis (96 suspected of having VL, 37 CL and one both VL and CL) were analyzed in our laboratory during 1992–2013 by microscopy, culture and, from 2005, also by real-time PCR. Leishmania spp. were detected in 23 samples of 15 patients (seven with VL and eight with CL), representing an infection rate of 11.2%. The figure of the cases of leishmaniasis herein reported, even if not comparable to that described for Italian areas other than Parma, underlines that suitable tools are mandatory for correct diagnosis. Moreover, the severity of this disease, particularly VL with its documented northward spread, requires physicians of continental Europe to increase their attention about the possibility of suspecting leishmaniasis in patients reporting related signs and symptoms and/or risk factors.